Evaluation of the Implementation of the Construction Safety Management System (SMKK) Based on Regulation of the Minister of Public Works and Housing No. 10 of 2021 in the Kesawan Old Town Residential Infrastructure Project, Medan - Nabila Syahlan; Robiana Modjo (JURNAL KESMAS DAN GIZI (JKG), 2026)
The construction sector is recognized as one of the industries with a high risk of occupational accidents due to the complexity of work activities, dynamic working environments, and the involvement of multiple stakeholders in project implementation. Data from the Ministry of Manpower of Indonesia show that occupational accident cases have increased in recent years, reaching 298,137 cases in 2022, 370,747 cases in 2023, and 462,241 cases in 2024. The construction sector contributed approximately 0.8% of cases in 2023 and 0.92% in 2024, equivalent to about 4,233 occupational accidents in construction services. This condition highlights the importance of implementing an effective construction safety management system to reduce workplace accidents. This study aims to evaluate the implementation of the Construction Safety Management System (SMKK) in the Kesawan Old Town residential infrastructure development project in Medan City based on the Regulation of the Minister of Public Works and Housing No. 10 of 2021. The study employed descriptive design with a mixed-method approach through field observations, document reviews, and interviews with relevant stakeholders. The research instrument used a monitoring and evaluation checklist with a binary scoring method. The results indicate that the completeness of SMKK documentation reached 97.8%, categorized as highly satisfactory, while field implementation achieved 100%. These findings demonstrate strong consistency between safety planning and its implementation in the project. However, improvements are still needed in worker health awareness programs and hazardous material inspection documentation.